Design and development of encoder sensor with graphical user interface (GUI) - Ihsan, Ahmad Zubir (2007)
MATLAB is one of the software that can create Graphical User Interface (GUI). The GUI will be designed using guide to create the layout editor. The objective of this project is to display the signal that is generated by encoder sensor in GUI. There are three phases to develop this project. Phase one is a development of the sensor circuit to produce signal in analogue form. The next phase is a construct of the controller circuit in order to convert the analogue signal to digital signal. In controller circuit it also used Intergrated Circuit (IC) MAX233. The function of the IC is to transmit or retrive the data from external device to the computer or vice versa and at the same time it remains the signal in stable condition by amplified the signal in order to reduce the losses and noise. At computer, DB9 used to connect with the port in computer. The changes of the signal form from analogue signal to digital signal are necessary because the computer only can accept the data in digital form. The final phase is a development of the GUI in MATLAB. In the end of this project, the signal generated by encoder sensor displayed in GUI. -Author